Comparison Of Quality Of Physical Tablet MetforminHydrochloride Trademark And Generic - Wijayanti, Fitri; , Dr. T.N. Saifullah S., M.Si., Apt; , Suprapto, M.Sc., Apt (2016)
Patent drugs are drugs that have recently been found by research and have the patent duration depends on the type of the medication. After a period of patented drugs to stop his patents, patent medicines and then later referred to as a generic drug. Most people assume that quality drugs are drugs that are expensive like product trademark. One example of a trademark drug and the generic drug metformin hydrochloride tablets is an oral antidiabetic medication. The test of physical characteristic was done in this research concludes the test of weight uniformity, thickness tablets, diameter, hardness tester, friability tester and disintegration tester. The result of the data are considered with the rules and regulation of Indonesian farmakope and the other books. The research result show products generic and products are trade having the difference in violence and time destroyed tablet but have in common in test uniformity weight, thickness, diameter, and friability tester. The quality of physical tablet metformin hydrochloride to the generic and a trade have met the requirements in control of the quality of tablet.